Community resources for energy transition: Implementing bioenergy villages in Germany. Issue 2 (2nd May 2018) - Roesler, Tim
Abstract : Innovations in energy transitions are diverse. Community‐led innovations have only recently gained more attention. In the German energy transition, the community‐led approach has resulted in a growing number of innovative renewable energy projects, with prominent examples including bioenergy villages. Although community‐led innovations only constitute a niche within the German energy regime, through the example of bioenergy villages we can see how this approach is able to significantly change the energy regime on a local scale. This paper explores the role of community‐led actions and resources in the implementation process of bioenergy villages in Germany, using the example of the county of Marburg‐Biedenkopf in Hesse. The conceptual background of this paper is based on the analytical frameworks of the multi‐level perspective and strategic niche management. Specifically, it addresses the two recent critiques on the neglect of space and place as well as the neglect of the analysis of community‐based actions. Using this perspective, the paper analyses the spatial and scalar linkages between local community‐driven actions and extra‐local resources.